With an Iron Broom: Cleansing Berlin's Bülowplatz of 'Judeo-Bolshevism', 1933–1936*. Issue 1 (14th January 2022) - Walch, Teresa
Abstract: Home to the Communist Party of Germany's headquarters and heart of the remaining Scheunenviertel and its Jewish populations, Berlin's Bülowplatz was detested as representative of 'Judeo-Bolshevism' by local Nazis, and they vowed to 'cleanse' the square with an 'iron broom'. In March 1933, SA-men and police officers occupied and confiscated the KPD headquarters and renamed the square 'Horst-Wessel-Platz'. Thereafter, city officials selected the Jewish-owned apartment buildings behind the square for the first urban renewal measures under the new regime, with the explicit intent of evicting the Jewish residents from this Nazi memorial square. Via a close reading of minutes from bureaucratic meetings, this article illuminates how bureaucrats began translating Nazi ideology into practice. Although municipal and federal bureaucrats initially lacked the requisite authority and legislation to implement this ideologically driven project, united by broadly held antisemitic prejudices they creatively devised solutions and collaborated to mobilize bureaucratic processes for city planning that was explicitly antisemitic. The ideological transformation of Bülowplatz constituted the earliest case of de-Jewification ( Entjudung ) in Nazi Germany and set an important precedent for later measures of spatial and ethnic cleansing enacted against Jews in Germany and across Europe.